SUSTAINABILITY ANALYSIS OF WHITELEG SHRIMP POND AQUACULTURE AT JATIRENGGO VILLAGE, LAMONGAN REGENCY - Evellin Dewi Lusiana; Muhammad Musa; Mohammad Mahmudi; Sulastri Arsad; Nanik Retno Buwono (Jurnal Ekonomi Pembangunan, 2018)
Whiteleg shrimp (Litopenaeus vannamei) is a fisheries commodity which has high economic value because of its high demand and easier cultivation. Lamongan regency is one of the minapolitan region in East Java Province, especially at Glagah district, Jatirenggo village which becomes the minapolist, with one of the superior commodities is whiteleg shrimp. The development of a certain village can be determined by village developing index or IDM which consists of three categories, they are left behind, developing, and advance village. Jatirenggo village has a village developing index (IDM) of 0.6080 which classified as developing category or category 2. Thus, in order to increase its status, the welfare of its people need to be considered. Whiteleg shrimp pond aquaculture can be one of the effort to increase the income of Jatirenggo’s. This study aims to analyze the sustainability of whiteleg shrimp aquaculture activity in Jatirenggo village according to ecology, socio-economic, technology-infrastructure, and institutional dimension. The used method was MDS Rapfish. The results showed that the whiteleg shrimp aquaculture in Jatirenggo village is classified as sustainable, or it means the situation in Jatirenggo village is suitable for a successful aquaculture. Thus, it can be expected to increase the income of the farmers.